Pengaruh variasi waktu pemeraman terhadap nilai uji kuat tekan bebas pada tanah lempung dan lanau yang distabilisasi menggunakan kapur pada kondisi tanpa rendaman (Unsoaked) - zulmi, karina apriliani puspa; Setyanto, Setyanto; afriani, Lusmeilia (Universitas Lampung, 2017)
Clays and silts have the low strength compressive. Clay is a kind of fine grain soil that has a low bearing capacity and very sensitive to changes in water content. To improve soil conditions then soil reinforcement is done by using lime substance. The clay soil sample is a type of high plasticity clay that taken from Rawa Sragi- Jabung- East Lampung district and then the silt soil sample is taken from Yosumulyo-East Metro- Metro City. Based on previous experiments, that soil is included in soft clay and high plasticity category. Based on Unified Soil Clasification (USCS), clay belong to CL category, While silts belong to Cl-ML category. In unconfined compressive strength test, clays and silts with variation of curing time and unsoaked condition, soil with hydrated lime mixtured with modified proctor compacted, for clays,Qu value increased with the addition of lime content. It get Qu optimum value increased when it has 12% hydrated lime content, 28 days of curing time. For silts Qu optimum value inscreased when it has 12% hydrated lime content and 28 days of curing time. Hydrated lime adding could inscred unconfined compressive strength but with longer curing time duration (28 days). Because the greater Qu soil value is the greater soil bearing capacity.Keywords: Hydrated Lime, Clay, Silt, Unconfined Compressive Strength, Soil Bearing Capacity